Mind the gap: sentencing, rehabilitation and civic purgatory - Henley, Andrew (Sage Publications, 2018)
This article discusses the relationships and tensions between the sentencing, statutory supervision and legal rehabilitation of lawbreakers under UK legislation. It does so with reference to both the Rehabilitation of Offenders Act 1974, which allows some criminal records to become ‘spent’ after a set period of time, and the Offender Rehabilitation Act 2014, which was designed to significantly expand statutory supervision arrangements. The article also demonstrates how, post-supervision, many former lawbreakers are cast into a state of ‘civic purgatory’, before suggesting that a more fully integrated approach to rehabilitation is required.